Thyroxine (T4) transfer from blood to cerebrospinal fluid in sheep isolated perfused choroid plexus: role of multidrug resistance-associated Proteins and Organic anion Transporting Polypeptides - Zibara, Kazem; El Zein, Nabil; Sabra, Mirna; Hneino, Mohammad; Harati, Hayat; Mohamed, Wael Mohamed Yousef; Kobeissy, Firas H.; Kassem, Nouhad (Frontiers Media SA, 2017)
Thyroxine (T4) enters the brain either directly across the blood–brain barrier (BBB) or indirectly via the choroid plexus (CP), which forms the blood–cerebrospinal fluid barrier (B-CSF-B). In this study, using isolated perfused CP of the sheep by single-circulation paired tracer and steady-state techniques, T4 transport mechanisms from blood into lateral ventricle CP has been characterized as the first step in the transfer across the B-CSF-B. After removal of sheep brain, the CPs were perfused with 125I-T4 and 14C-mannitol. Unlabeled T4 was applied during single tracer technique to assess the mode of maximum uptake (Umax) and the net uptake (Unet) on the blood side of the CP. On the other hand, in order to characterize T 125 4 protein transporters, steady-state extraction of I-T4 was measured in presence of different inhibitors such as probenecid, verapamil, BCH, or indomethacin. Increasing the concentration of unlabeled-T4 resulted in a significant reduction in Umax%, which was reflected by a complete inhibition of T4 uptake into CP. In fact, the obtained Unet% decreased as the concentration of unlabeled-T4 increased. The addition of probenecid caused a significant inhibition of T4 transport, in comparison to control, reflecting the presence of a carrier mediated process at the basolateral side of the CP and the involvement of multidrug resistance-associated proteins (MRPs: MRP1 and MRP4) and organic anion transporting polypeptides (Oatp1, Oatp2, and Oatp14). Moreover, verapamil, the P-glycoprotein (P-gp) substrate, resulted in ~34% decrease in the net extraction of T4, indicating that MDR1 contributes to T4 entry into CSF. Finally, inhibition in the net extraction of T4 caused by BCH or indomethacin suggests, respectively, a role for amino acid “Lsystem and MRP1/Oatp1 in mediating T4 transfer. The presence of a carrier-mediated transport mechanism for cellular uptake on the basolateral membrane of the CP, mainly P-gp and Oatp2, would account for the efficient T4 transport from blood to CSF. The current study highlights a carrier-mediated transport mechanism for T4 movement from blood to brain at the basolateral side of B-CSF-B/CP, as an alternative route to BBB.